A history of criminal law in New South Wales - Woods, Gregory D. (The Federation Press, 2002)
New South Wales was from its origins uniquely connected with the criminal law. The first volume of this study (Woods, 2002) covered the period from 1788 until Federation - convicts, gold rushes, wild bushrangers and equally wild legislators. This second volume continues the still-fascinating story from 1901 (when the colony became a state) through until mid-20th century, when the death penalty was effectively abolished. Once again the author draws on his wide experience of the criminal law as an academic, law reformer, barrister and judge to describe the development of the law in its social, economic and political contexts. There are various broad themes, including: the regular disputes in the body politic about what conduct should attract criminal punishment. Should it be a crime to avoid vaccination against deadly diseases? To go on strike, or to try to monopolise an industry? To defame someone? the two world wars, and their impacts; the gradualism of change in the criminal law outside wartime. The author engages with the technicalities, but relates these intriguingly to the characters who inhabit the world of criminal practice, the courts and the gaols. John Norton and Paddy Crick are on the loose again for the first time since 1958, when Cyril Pearl immortalised them in Wild Men of Sydney. Here each has his own chapter, as does Jimmy Governor, the inspiration for Thomas Keneally's The Chant of Jimmie Blacksmith. Other chapters deal with Woolcott Forbes, the famous corporate fraudster of the 1930s and 1940s known in the press as "The Bullfighter"; a policeman with the improbable name of Mendelssohn Bartholdy Miller; and Major Charles Cousens, the plum-voiced prisoner-of-war and radio announcer who was forced to broadcast from Tokyo during the Second World War and who faced charges of treason when he was returned to Australia at war's end